PENEGAKAN HUKUM TINDAK PIDANA PENCURIAN LISTRIK BERDASARKAN UNDANG-UNDANG NOMOR 30 TAHUN 2009 TENTANG KETENAGALISTRIKAN DI WILAYAH HUKUM KOTA BANGKINANG - Destriadi, Ari; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Community needs at this time is always increasing, one of them was the needs of electrical power. Electrical power is a basic needs for the entire community, this can be seen from the number of electronic equipment used in everyday life which aims to facilitate all activities. The high level of needs for electricity have a negative impact, such as the crime of theft of electricity. To do law enforcement efforts against crimes of theft of electricity is always having problems. The purpose of this essay is to determine the factors that cause the occurrence of the crime of electricity theft and to know the law enforcement criminal offense of theft of electricity in the jurisdiction of the Bangkinang City.This type of research can be classified in types of socio-juridical research, because in this study the author directly research on the location or place that is examined in order to provide a complete and clear description of the problems researched. This research was conducted in the law area of the city of Bangkinang, while population and the sample is the entire parties relating to issues that are examined in this study, the data source used, the primary data, secondary data, and tertiary data, techniques of collecting data in this study with interviews and research librarianship.From the results of research that the author do can be concluded, first is the factor that cause the criminal offense of theft of electricity is an economic factor, factor of the convoluted electrical installation procedures, factor of environmental, factor of the weakness of law enforcement and factor of electric power installation bureau. The second, law enforcement of criminal offense of electricity theft in the law area of Bangkinang city does not run at all because the PLN as the victim who suffers losses does not bring the case to the realm of law and settle the case and only apply sanctions based on the Decision of the Board of Directors of PT. PLN (Persero) No. 1486. K/DIR/2011 about the Control of Electricity Usage.Keywords: Law Enforcement - Criminal Offense-Theft of Electricity